PENGARUH PENGALAMAN, IDEALISME, DAN KOMITMEN PROFESIONAL TERHADAP SENSITIVITAS ETIKA AUDITOR - Goo, Theresia Yunita Wea; Banda, Falentina Lucia (Program Studi Akuntansi Universitas Flores, 2022)
The purpose of this study was to find out whether the auditor's experience, auditor idealism and auditor's professional commitment have a positive effect on the sensitivity of auditor ethics in the Inspectorate of Nagekeo Regency and Ende Regency. The population in this study were all employees at the Inspectorate Office of Nagekeo Regency, totaling 52 people and 45 people at the Inspectorate Office of Ende Regency. So that a total of 97 people. The sampling technique used purposive sampling method, namely employees who have functional duties, namely auditors at the Inspectorate of the Nagekeo Regency, totaling 17 people and 17 people at the Inspectorate of Ende Regency. So that the total respondent is 34 people. This type of research uses a quantitative approach. This study uses primary data, namely a questionnaire. Data were analyzed using multiple linear regression analysis which was processed through IMB SPSS Statistics ver 25. The results of this study indicate that: (1). Experience has a positive and significant effect on Ethical Sensitivity, this is evidenced by the test results which show the coefficient value of the auditor's experience variable is 0.639 with > (3.269>1.69726) and a significant level of 0.003 <0.05. (2). Idealism has a positive effect on Ethical Sensitivity, this is evidenced by the test results which show the coefficient value of the auditor's idealism variable of 0.307 with > (2.053 > 1.69726) and a significant level of 0.049 <0.05. (3). Professional commitment has a positive effect on the auditor's ethical sensitivity, this is evidenced by the test results showing the coefficient value of the professional commitment variable is 0.426 with > (2.745 > 169726) and a significant level of 0.010 <0.05. Simultaneously the variables of experience, idealism and professional commitment to the auditor's ethical sensitivity are 38.6% while the remaining 61.4% is influenced by other variables not included in the study.